2023
DOI: 10.9734/ajess/2023/v49i41196
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Inclusive Accounting Education through the Integration of Stem Principles for a Diverse Classroom

Olubukola Omolara Adebiyi,
Samuel Oladiipo Olabanji,
Oluwaseun Oladeji Olaniyi

Abstract: In recent times, accounting education has explored many innovative approaches to address the collective needs of students. Integrating STEM (Science, Technology, Engineering, and Mathematics) principles in accounting education promises an increased potential for technology-driven solutions, enhanced learning strategies, and inclusivity. This study investigated the effects of integrating STEM principles into accounting education. The specific objective was to understand the impact of STEM integration on student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Among these, tools like ChatGPT, Claude, Bard, Copilot, and Copy.ai have emerged as significant players, each with unique capabilities and user interfaces. While these tools offer numerous benefits, including enhanced efficiency, personalized experiences, and innovative solutions across various sectors, their widespread adoption raises critical questions and challenges [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, tools like ChatGPT, Claude, Bard, Copilot, and Copy.ai have emerged as significant players, each with unique capabilities and user interfaces. While these tools offer numerous benefits, including enhanced efficiency, personalized experiences, and innovative solutions across various sectors, their widespread adoption raises critical questions and challenges [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This white paper also underscores the importance of identity protection and how their system adapts as applications and devices shift to the cloud. Moreover, EyeLock's introduction of new reference designs for iris authentication solutions indicates ongoing advancements and adaptability in cloud-based biometric systems [24,25]. However, while these reports provide insights into specific products, they might lack a broader industry perspective, often focusing on individual solutions rather than a comprehensive analysis of the field.…”
Section: Accuracy Variability Across Cloud Platformsmentioning
confidence: 99%
“…Eregha & Mesagan [2] investigated the position of various energydependent economies in Africa. They demonstrated that economic output is positively and dramatically impacted by energy usage and oil prices [27].…”
Section: Review Of Literaturementioning
confidence: 99%